WHOLE-GENOME SEQUENCING OF CLINICAL Mycobacterium tuberculosis ISOLATES WITH DIFFERENT DRUG SENSITIVITY PROFILES - Kozhamkulov , U.; Kairov , U.; Yerezhepov , D.; Akhmetova , A.; Molkenov , A.; Akilzhanova , A. (Eurasian Journal of Applied Biotechnology, 2016)
Tuberculosis (TB) remains a major cause of morbidity and mortality in many countries and thus, represents a major public health problem in Kazakhstan and globally. An alternative and more promising option in the fight against this disease is the application of genetic diagnostic methods, for example, the detection of point mutations or other genetic determinants of TB drug resistance and genotyping of M. tuberculosis. Whole-genome sequencing and next-generation sequencing (NGS) technologies have developed rapidly in recent decades and are now applied in many branches of biomedical research. New NGS technologies allow us to study whole-genome sequences of pathogens associated with various infectious diseases, to study their molecular and genetic features, and thus, to understand these pathogens on a fundamental and practical basis in terms of microbiology, virology, and epidemiology. This paper describes the application of high-performance “shotgun” next-generation sequencing, using a Roche 454 GS FLX + Titanium platform to determine the complete genome sequences of twenty clinical isolates of M. tuberculosis with different drug sensitivity profiles. The paper furthermore defines the quality indicators of genome sequencing, describes the de novo assembly of the complete genomes of M. tuberculosis isolates, and details the mapping and alignment to the reference genome of M. tuberculosis (H37Rv strain; GenBank database). The assembled genomes of two M. tuberculosis isolates were deposited in the NCBI GenBank database and are available for public access under the numbers AZBA00000000 and AZAZ00000000. The other genomes are available on request.